The Advanced Designs of Magnetrons with Improvement Output Characteristics - Churyumov, G. I.; Gerasimov, V.; Frolova, T. I.; Gritsunov, A. V.; Ekezli, A. (My University, 2016)
This paper presents the experimental and theoretical investigations of the two constructions of the magnetrons: the low-voltage X and Ku ranges magnetrons with two RF outputs of energy and the cold secondary emission cathode magnetron with ancillary side cold cathode. It is shown that the electronic frequency tuning in the magnetrons with two RF output can be obtained in the range more than 200 MHz. The electronic control of the frequency tuning from pulse to pulse is performed by the microwave switch on basis the p-i-n diodes. By using the computer modeling, the features of secondary emission multiplication mechanism of the electron beam at the front and droop of anode voltage pulses are shown. The prospects for developing such magnetrons and expansion of areas of their application are discussed.
Keywords: magnetron; cold cathode; electronic frequency tuning